Optimalisasi Pembuatan Pelet Regular Dari Limbah Biji Kopi Menggunakan Metode Value Stream Mapping Di Perusahaan Minuman Kopi Tangerang - Hartono Hartono; Huda Arief Anggoro2 (Program Studi Teknik Industri Universitas Muhammadiyah Tangerang, 2026)
ABSTRACT This study aims to optimize the production process of regular pellets made from coffee bean waste at a beverage company in Tangerang by applying the Value Stream Mapping (VSM) method. The research was motivated by the low production efficiency rate, which only reached 63% of the target, due to lengthy process flows, significant waiting times, and dominant non-value-added (NVA) activities. VSM was used to map the production flow, identify waste, and propose improvements through a Future State Map. The findings reveal that eliminating the oven process identified as the primary bottleneck and replacing it with a direct air-drying system in the silo significantly improved efficiency. Output productivity increased by 75%, from 3.14 kg/min to 5.49 kg/min, while the Process Efficiency Cycle (PEC) rose from 69% to 86%. The implementation of the Future State Map resulted in a more streamlined and integrated production flow, supporting green industry and circular economy principles. Keywords: Value Stream Mapping, coffee bean waste, pellet, production efficiency, lean manufacturing